2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.259895
|View full text |Cite
|
Sign up to set email alerts
|

Functional Infrared Imaging for Skin-Cancer Screening

Abstract: Annually 133.000 people world-wide get sick on malign melanoma, tendency increasing. The purpose of this study is the early diagnosis of malignant skin cancer. At the moment the dermatologists are screening for anomalies at the relevant lesion by examining the skin area with a microscope. To determine changes, another scan has to be taken in a follow-up session after a time period of about 15-20 weeks. Today's visual diagnostic decision is based on the pragmatic ABCD approach (Asymmetry, Border, Colour, and Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 8 publications
1
43
0
1
Order By: Relevance
“…For instance, Di Carlo [22] designed a thermostimulation method that solves the problem of false-negative results, and this method allows IR imaging to differentiate malignant melanoma from other types of pigmented lesions. Buzug et al [23] used cold gel packs to produce a substantial temperature difference on the skin surface for detection of melanoma and basal cell carcinoma. Also Santa Cruz et al [25] showed that dynamic infrared imaging is capable of following-up nodular melanoma patients treated with Boron Neutron Capture Therapy (BNCT).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Di Carlo [22] designed a thermostimulation method that solves the problem of false-negative results, and this method allows IR imaging to differentiate malignant melanoma from other types of pigmented lesions. Buzug et al [23] used cold gel packs to produce a substantial temperature difference on the skin surface for detection of melanoma and basal cell carcinoma. Also Santa Cruz et al [25] showed that dynamic infrared imaging is capable of following-up nodular melanoma patients treated with Boron Neutron Capture Therapy (BNCT).…”
Section: Introductionmentioning
confidence: 99%
“…[1] Both hypervascularity and these metabolic aberrations may explain increased temperature in these lesions. [2,3] However, thermal findings are difficult to quantify and to document objectively by clinical exam. Imaging of infrared (IR) radiation, or thermography, can permit objective temperature measures.…”
Section: Introductionmentioning
confidence: 99%
“…Thermography has been explored for imaging metastatic and primary melanomas since the 1970s, with published work suggesting that it may be helpful in diagnosis of primary and metastatic cutaneous melanomas. [3][48] IR thermography studies of primary melanomas suggest that lesion hyperthermia correlates with thickness of primary melanomas and that nodular primary melanomas are consistently hyperthermic. [9,10][11] Additionally, hyperthermic lesions have been associated with increased lymph node positivity.…”
Section: Introductionmentioning
confidence: 99%
“…CM is one of the most prominent noninvasive in vivo biomedical imaging modalities that can perform optical sectioning of human skin in the horizontal plane with a resolution comparable to that of histology. Its depth sectioning capability and reflection or fluorescence sensitivity can be utilized for cancer diagnosis in thin (~200-300 µm) samples [14][15][16]. CM systems offering cellular resolution have been successfully employed in several clinical investigations to identify nonmelanoma skin lesions and to monitor treatment responses in vivo [17].…”
Section: Imaging In Dermatologymentioning
confidence: 99%